2020
DOI: 10.1177/0907568220901758
|View full text |Cite
|
Sign up to set email alerts
|

Walking a thin line: Taking children’s decision to marry seriously?

Abstract: This article provides empirical evidence on children’s agency and capacity in making the decision to marry. Case studies from my fieldwork in Bali contrast the commonly represented image of child marriage as a forced marriage, by demonstrating that in many cases children themselves make the decision to marry. However, considering social power dynamics, is such a decision really the child’s? The analysis shows that the current international child marriage framework fails to walk the thin line between empowermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
12
0
2
Order By: Relevance
“…Moving forward, future empirical research on child marriage needs to investigate the contextualized realities of this practice, including to put the focus on investigating young people's sexualities and the agency of young people in determining with whom, when, and how marriage occurs (see Colquhoun and Nilan 2020 in this edition). Through this, as informed by previous research in Indonesia (see Horii 2019Horii , 2020Grijns and Horii 2018), future social policies can offer a range of alternatives in addressing the harmful impacts of child marriage beyond regulating the minimum age as envisaged by the dominant discourse. By focusing on banning child marriage, social policies obscure the diverse social realities, tend to drive the practices underground (see Boyden et.…”
Section: Concluding Notes: Indonesian and Global South Girls Beyond Vmentioning
confidence: 94%
See 4 more Smart Citations
“…Moving forward, future empirical research on child marriage needs to investigate the contextualized realities of this practice, including to put the focus on investigating young people's sexualities and the agency of young people in determining with whom, when, and how marriage occurs (see Colquhoun and Nilan 2020 in this edition). Through this, as informed by previous research in Indonesia (see Horii 2019Horii , 2020Grijns and Horii 2018), future social policies can offer a range of alternatives in addressing the harmful impacts of child marriage beyond regulating the minimum age as envisaged by the dominant discourse. By focusing on banning child marriage, social policies obscure the diverse social realities, tend to drive the practices underground (see Boyden et.…”
Section: Concluding Notes: Indonesian and Global South Girls Beyond Vmentioning
confidence: 94%
“…Various studies have shown the role of young people's agency as an important aspect in determining with whom, when, and why marriages occur. Several case study research in Bali and West Java found that in many cases, young people were the ones who made the decision to get married, and in their perspective, their marriage is not considered as forced marriage (Horii 2020;Grijns et al 2016). Moreover, Grijns et al (2016) identify a typology of child marriages in West Java based on young people's agency, firstly are love matches of young people who chose their own partners as well as marriages inspired by orthodox beliefs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations